Willingness to Pay the Organic Vegetable: The Impact of Covid-19 Pandemic in Indonesian Experience - Ridwan LUTFIADI; Ahya KAMILAH; Nana DANAPRIATNA (International Journal of Environmental, Sustainability, and Social Science, 2023)
The enthusiasm for maintaining health has increased in line with the Covid-19 pandemic, though they have to pay the higher price. Therefore, study aims to determine changes in people's behavior in consuming organic vegetables due to Covid-19, willingness to pay (WTP) and factors that influence. The research was conducted in three stages--descriptive socio-demographic factors, calculation of WTP with the Contingent Valuation Method approach and SEM (Structural Equation Modeling) analysis. Based on 155 respondents who determined by Slovin formula and accidental sampling technique. The study showed that consumers had a higher WTP for various types of organic vegetables, especially spinach, chayote, and kale. However, this WTP is significantly influenced by level of education, type of work and income. Consumer behavior significantly affected WTP for organic vegetables during Covid-19 pandemic. Thus, Covid-19 pandemic provides great potential for an increase in the number of consumption and purchases of organic vegetables.